"Assessing the methodological quality of systematic reviews in radiation oncology: A systematic review". (October 2017) - Hasan, Haroon; Muhammed, Taaha; Yu, Jennifer; Taguchi, Kelsi; Samargandi, Osama A.; Howard, A. Fuchsia; Lo, Andrea C.; Olson, Robert; Goddard, Karen
Highlights: Systematic reviews with methodological flaws can misinform evidence-based medicine. Systematic reviews in Radiation Oncology are of less than fair quality based on AMSTAR. Meta-analyses in Radiation Oncology are of fair to good quality based on AMSTAR. Decision-makers should scrutinize the quality of systematic reviews and meta-analyses in evidence-based medicine. Abstract: Objective: The objective of our study was to evaluate the methodological quality of systematic reviews and meta-analyses in Radiation Oncology. Methods: A systematic literature search was conducted for all eligible systematic reviews and meta-analyses in Radiation Oncology from 1966 to 2015. Methodological characteristics were abstracted from all works that satisfied the inclusion criteria and quality was assessed using the critical appraisal tool, AMSTAR. Regression analyses were performed to determine factors associated with a higher score of quality. Results: Following exclusion based on a priori criteria, 410 studies (157 systematic reviews and 253 meta-analyses) satisfied the inclusion criteria. Meta-analyses were found to be of fair to good quality while systematic reviews were found to be of less than fair quality. Factors associated with higher scores of quality in the multivariable analysis were including primary studies consisting of randomized control trials, performing a meta-analysis, and applying a recommended guideline related to establishing a systematic review protocol and/or reporting. Conclusions: Systematic reviews and meta-analyses may introduce a high risk of bias if applied to inform decision-making based on AMSTAR. We recommend that decision-makers in Radiation Oncology scrutinize the methodological quality of systematic reviews and meta-analyses prior to assessing their utility to inform evidence-based medicine and researchers adhere to methodological standards outlined in validated guidelines when embarking on a systematic review.